(untitled) (Journal Of Educational and Psychological Researches, 2023)
Abstract The aim of the current research is to identify the level of administrative applications of expert systems in educational leadership departments in light of the systems approach. To achieve the objectives of the research, the descriptive-analytical and survey method was adopted. The results showed that the level of availability of the knowledge base for expert systems in educational leadership departments (as inputs) was low. The level of availability of resources and software for expert systems in educational leadership departments (as transformational processes) came to be low, as well as the level of availability of the user interface for expert systems in educational leadership departments (as outputs) recorded a low degree. In light of the results of the research, the researcher recommended the necessity of holding continuous training courses for heads of educational leadership departments on how to take advantage of modern technologies and expert systems, including the applications of expert systems in educational institutions, as one of the helping factors in supporting decision-making, educating leaders about how to improve the use of Technology in management and leadership.